Trans(gender) journeys: rights and the (non-)recognition of “human” - Rodrigues, Liliana; Pinho, Ana R.; Carneiro, Nuno Santos; Nogueira, Conceição (Frontiers in Sociology, 2023)
A human right paradigm has been challenging the biomedical perspectives that tend to be normalized in the Western context concerning the lives of trans people. The aim of this study is to understand how trans people in Portugal and Brazil perceive the (non-)recognition of their socio-cultural, economic and political rights. Specifically, the study intends to know in what extent these perceptions influence the processes of identity (de)construction. For this purpose, 35 semi-structured interviews were conducted with people self-identified as trans, transsexuals and transvestites in Brazil and Portugal. The narratives of the participants were analyzed according to the thematic analysis method and the following six main themes emerged: (i) Who are the rights for; (ii) Types of rights; (iii) Paradigm of distribution of rights; (iv) Local or global rights; (v) Non-recognition of the “human”; and, (vi) Transphobias (and cissexism). The results allowed the knowledge of rights and the non-recognition of the “human” which is the central organizer of the analysis. Among the main conclusions of this study, we emphasize the circumscription of rights to certain international, regional and/or national contexts; the existence of local instead of global rights, since they are influenced by regional and international law, but they depend on the legislation in force in each country; and the way human rights can also be understood as a platform of invisibility and exclusion of other people. Based on a commitment to social transformation, this article also contributes to rethinking the violence that is exercised on trans people as a continuum, whether through ‘normalizing devices' by medical contexts, family contexts, public space, or even through internalized transphobia. Social structures produce and sustain transphobias and, simultaneously, are responsible for fighting them by changing the paradigm about the conception of transsexualities.